Creating an Effective English Environment for Indonesian Speakers: Strategies and Challenges - Sudirman (ASIAN PUBLISHER, 2024)
The purpose of this study is to analyze effective strategies for creating an English environment for Indonesian speakers and to identify the challenges that hinder its implementation in EFL contexts. Using a qualitative literature review method, this research synthesizes findings from empirical studies, theoretical papers, and pedagogical reports related to language exposure, immersive learning, and English teaching practices in Indonesia. The results reveal that successful English environments are characterized by consistent classroom exposure, technology-assisted learning, school–home collaboration, and communicative activities that reduce anxiety and increase engagement. However, several challenges persist, including limited resources, inadequate teacher proficiency, learners’ psychological barriers, and weak parental involvement. These findings highlight the need for more systemic and integrative approaches to strengthen English exposure for Indonesian learners.